ANALISIS PEMBOROSAN MENGGUNAKAN METODE LEAN SERVICE PADA CORE WAREHOUSE DI PT.SIGMA CIPTA UTAMA - Riyadh Widatama, - (2019)
PT. Sigma Cipta Utama (SCU) is a business company that starts with data management in the oil and gas industry. This company provides a variety of data management services including storage and management, especially rock samples of exploration and production (core), this service continues to make improvements oriented to the presentation of information and others. Based on observations made in this study, there are still several work process activities that cause waste in the core maintenance unit warehouse department resulting in waiting in the work process for storage services, demand services and return services for exploration rock sample data. This study aims to identify waste, analysis of supporting factors and recommendations for improvement as an effort to improve. By using the concept of lean service research starting from describing the state map (BPM), and weighting the current wastage, the weight of waste is analyzed using the VALSAT matrix to identify waste in the system, to analyze the causes of waste with a fish bone diagram. The results of the study show that the two wastes that often occur are deffects with an average score of 5 and unnecessary motions with an average score of 4. Proposals for improvement from research in the sample of activities carried out can save time value added from 25 hours to 20.2 hours and necessary but non value added from 214 hours to 185.3 hours.